A comparative study on it outsourcing models for Malaysian SMEs e-business transformation - Sabri S.M.; Sulaiman R.; Ahmad A.; Tang A.Y.C. (Asian Research Publishing Network, 2023)
Today business state has become more dynamic and venturing into e-business is one of business requirements that promote business efficiency and opportunities. This has also affected the SMEs which are known to have limitations in terms of resources and skills to develop in-house IT applications. Information Technology Outsourcing (ITO) could be one of the solutions to accelerate the adoption process among the SMEs. Thus, the aim of this research is to investigate the factors affecting the decision to deploy ITO services among the Malaysian SMEs for e-Business implementation. A qualitative approach is used to explore the level of awareness, potential and implication of implementing the ITO among the SMEs. The focus of this study is companies that within Halal Industries. This paper discusses the comparative study on existing e-business and ITO models and current practices to identify factors and research gaps in this area. Findings from this comparative study are the reference model and the factors to being considered for this research. The considered factors will be used to construct data instruments and as a basis for the proposed model for this research.